Targeted thrombolysis by magnetoacoustic particles in photothrombotic stroke model - Choi, Won Seok; Cho, Hyeyoun; Kim, Gahee; Youn, In chan; Key, Jaehong; Han, Sungmin (The Korean Society for Biomaterials | BioMed Central, 2022)
Background Recombinant tissue plasminogen activator (rtPA) has a short half-life, and additional hemorrhagic transformation (HT) can occur when treatment is delayed. Here, we report the design and thrombolytic performance of 3 μm discoidal polymeric particles loaded with rtPA and superparamagnetic iron oxide nanoparticles (SPIONs), referred to as rmDPPs, to address the HT issues of rtPA. Methods The rmDPPs consisted of a biodegradable polymeric matrix, rtPA, and SPIONs and were synthesized via a top-down fabrication. Results The rmDPPs could be concentrated at the target site with magnetic attraction, and then the rtPA could be released under acoustic stimulus. Therefore, we named that the particles had magnetoacoustic properties. For the in vitro blood clot lysis, the rmDPPs with magnetoacoustic stimuli could not enhance the lytic potential compared to the rmDPPs without stimulation. Furthermore, although the reduction of the infarcts in vivo was observed along with the magnetoacoustic stimuli in the rmDPPs, more enhancement was not achieved in comparison with the rtPA. A notable advantage of rmDPPs was shown in delayed administration of rmDPPs at poststroke. The late treatment of rmDPPs with magnetoacoustic stimuli could reduce the infarcts and lead to no additional HT issues, while rtPA alone could not show any favorable prognosis. Conclusion The rmDPPs may be advantageous in delayed treatment of thrombotic patients.